QUALITATIVE RESEARCH IN THE DEVELOPMENT AND IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN ECONOMY - Ana-Maria NEDELCU (Challenges of the Knowledge Society)
We are currently feeling the effects of the Fourth Industrial Revolution (4IR) which has undergone considerable improvements as a result of the advancement of artificial intelligence and its related technologies, as well as other disruptive technologies components of Industry 4.0. The impact that artificial intelligence has had on humanity is spectacular, given that it is a much more present element in our lives than we would have thought. From translation software to virtual assistants (Siri, Cortana, etc.) artificial intelligence makes its presence felt and improves the way we live, communicate and work. Robotics is the most extensive field related to artificial intelligence and deals with the study and development of robots. They have great potential in improving the quality of our lives both at home and at work, and robots that work with human colleagues will help create new jobs and improve existing ones, giving people more time to focus on other activities. Collaboration in the process of work between man and robot will lead to the mutual completion of skills on both sides. In this paper I will address topics such as artificial intelligence, automation, robotics, the impact of robots on jobs and as a practical part of the paper I will conduct a qualitative research on companies' perceptions of the adoption of artificial intelligence technologies.